2015
DOI: 10.1002/jcp.25024
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Osteoblast Migration Involving Receptor Activator of Nuclear Factor‐kappa B (RANK) Signaling

Abstract: Bone remodeling requires osteoclast activation, resorption, and reversal, prior to osteoblast migration into the bone pit. The Receptor Activator of NF-κB (RANK) signaling pathway plays an important role in bone remodeling. Two components of the RANK signaling pathway, RANK Ligand (RANKL) and the decoy receptor Osteoprotegerin (OPG), are expressed predominantly on the surface of osteoblasts, while RANK is principally expressed on the surface of osteoclasts. However, RANK has also been reported to be expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 58 publications
(91 reference statements)
1
13
0
1
Order By: Relevance
“…RANK is over-expressed on osteosarcoma, 15 , 16 a mesenchymal tumor with the osteoblastic origin and regulates osteoblast migration, 16 essential to bone modeling and remodeling. The current studies imply that RANKL signaling could play a key role in osteoblastic differentiation and bone formation, which has long been underestimated.…”
Section: Introductionmentioning
confidence: 99%
“…RANK is over-expressed on osteosarcoma, 15 , 16 a mesenchymal tumor with the osteoblastic origin and regulates osteoblast migration, 16 essential to bone modeling and remodeling. The current studies imply that RANKL signaling could play a key role in osteoblastic differentiation and bone formation, which has long been underestimated.…”
Section: Introductionmentioning
confidence: 99%
“…These authors demonstrated that RANKL produced by osteoblasts and bone marrow stromal cells attracts RANK-expressing cancer cells and induces their migration. This mechanism seems to be relatively universal and was observed in prostate cancer [ 95 , 126 , 127 ], breast cancer [ 95 ], colon cancer [ 58 ], melanoma [ 95 ], oral squamous carcinomas [ 128 ], lung cancer [ 129 ], hepatocarcinoma [ 130 ], endometrial cancer [ 131 ], osteosarcoma [ 132 , 133 ] and renal cancer [ 134 ]. RANKL-induced migration is associated with specific signalling cascades, especially the activation of MAP Kinase pathways.…”
Section: Rank/rankl and Cancermentioning
confidence: 99%
“…The receptor activator of the nuclear factor kappa B ligand (RANKL) is another factor mediating osteoblast migration. It induces chemotactic migration of the human osteoblast cell line hFOB 1.19 and the primary human osteoblast through activating phosphorylation of extracellular signal-regulated kinase (ERK), p38 (MAPK), Akt, and p65 (NF-κB) [33]. Furthermore, BMP-2 could stimulate in vitro migration of the human primary osteoblasts isolated from trabecular bone in a dose-dependent manner, suggesting BMP-2 might be involved in the chemotactic recruitment of osteoblasts during bone formation in addition to its function as a differentiation enhancer [34] (Table 1).…”
Section: The Overview Of Msc Migration During Bone Formationmentioning
confidence: 99%